Pengaruh Durasi Live, Interaksi Live, dan Keterlibatan Emosional terhadap Pembelian Implusif pada Konsumen TikTok Generasi Z - Zaki Pandu Pangestu; Fajar Nurwibowo; Rony Triwibowo (Institut Agama Islam Nasional Laa Roiba Bogor, 2026)
The development of social commerce is acting as a catalyst for transformations in consumer purchasing habits, with the strongest impact observed among Generation Z consumers, who actively use TikTok. The live streaming feature not only functions fas a promotional tool but also creates interactive and emotional experiences that can trigger impulsive purchases. This study seeks to assess the effect of TikTok live-streaming duration on Generation Z. The study useduUsing a quantitative research design that integrates survey data with multiple linear regression techniques. The results show that live duration and live interactions have practical implications for digital business actors in optimizing live streaming strategies as an effective marketing tool.